Hypokalaemic Periodic Paralysis– A Prospective Study of the Underlying Etiologies - Jandhyala, Surya Narayana (J Clin Diagn Res, 2015)
BACKGROUND: Hypokalaemic periodic paralysis (HPP) is a rare muscular disorder characterised by episodic weakness associated with hypokalaemia. The disease can either be inherited or acquired and misdiagnosis of the disease is quite common. Most of the data available on the disease is from the western world. Studies reporting aetiological, clinical and metabolic profiles of Indian population are sparse. Hence we tried to provide insights of the disease among the Indian population. AIM: To study the aetiological, clinical and metabolic profile of patients diagnosed with Hypokalaemic Periodic Paralysis (HPP). MATERIALS AND METHODS: This is an observational and analytical study on HPP diagnosed patients, during September 2011 to September 2014 in Kasturba Hospital, Manipal. A total of 23 patients were studied. Detailed history, clinical evaluation and metabolic workup for secondary causes of HPP were analysed. RESULTS: Of the 23 patients, 57% had primary HPP while 43% had secondary HPP. The group of patients with primary HPP comprised of 92% males and 8% females with mean age of 28 years and the mean duration of symptoms of 18 hours. The group with secondary HPP comprised of 70% males and 30% females with mean age of 38.7 years and the mean duration of symptoms of 60 hours. The secondary causes of HPP were thyrotoxicosis (50%), infective diarrhea (20%), Crohn’s disease (10%), renal tubular acidosis (RTA) Type I (10%) and Conn’s syndrome (10%). CONCLUSION: In our study primary HPP was found to be more common than secondary HPP. Males were predominantly affected in both groups. HPP should be ruled out before starting therapy for Guillain-Barré Syndrome (GBS).